The Effect of Strengthened Corporate Governance on Firm Performance in the United States - Pandya, Dishant; Van Deventer, Ian Andrew (Journal of Accounting, Business and Finance Research, 2021)
In response to the accounting scandals of the late 1990s, regulators adopted changes to corporate governance rules in 2003 in an effort to restore investor confidence in the stock market. The purpose of this study is to determine whether the changes to board leadership structure imposed on U.S. companies affected firm performance as measured by operating return on assets. This study was conducted with a sample of 857 publicly traded companies listed on the New York Stock Exchange and 11,632 firm-year observations over the period from 1997 to 2012. Using a difference-in-difference estimator and multivariate analysis, we found a positive and significant indication that changes to board leadership structure improved the long-run performance of firms that were previously insider controlled. The results of this study indicate that some firms were not ideally structured prior to 2003 when the changes in corporate governance rules took effect for publicly traded companies listed on the New York Stock Exchange.